Effects of information and communication technology on total-factor carbon emission efficiency and the health co-benefits - Linghu, Jingying; Wojewodzki, Michal; Cheong, Tsun Se (Frontiers in Public Health, 2024)
Information and communication technology (ICT) has great potential to propel economic development toward a low-carbon direction. This study aims to investigate the effect of ICT development on total-factor carbon emission efficiency (TFCEE), as well as its public health co-benefits. We use dynamic (threshold) models and a panel of 30 Chinese provinces from 2008 to 2019. The results suggest that ICT significantly and positively impacts the TFCEE. Specifically, for every 10 per cent increase in the internet development index, the TFCEE increases by 0.11 per cent. Moreover, we find that ICT development indirectly improves the TFCEE by promoting green innovation and energy structure optimization. Furthermore, when green innovation (energy structure represented by the share of coal) switches from below to above (above to below) its threshold value, the promotion effect of ICT development on the TFCEE increases. Additionally, the results show that improving the TFCEE can lead to co-benefits in strengthening China's public health. This study delivers novel insights on promoting the TFCEE through the ICT channel and highlights its positive health-related externalities. Furthermore, we offer policy recommendations to Chinese decision-makers, which can apply to other emerging economies battling similar issues.